2022
DOI: 10.1007/s12594-022-2184-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional b-value and Fractal Dimension Mapping of the Uttarakhand Himalayan Region

Abstract: The 3-D distributions of b-value of the frequency-magnitude distribution and fractal correlation dimension (D2) of seismically active Uttarakhand Himalayan seismic zone is presented. For this study, a catalogue of 525 local earthquakes was used (ML1.0-5.5) during 2017-2020. The de-clustered catalog is found to be complete above ML=2.6. The b-value is estimated to be 0.82±0.06 by maximum likelihood method. The modelled b- and D2 estimates in the study area range from 0.35 to 1.524 and 0.29 to 1.71, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The smaller b-value zones (0.48–0.60) are corroborated with higher D 2 (1.5–1.9), implying negative correlation. The areas with low b-value and high D 2 and are expected to accumulate prominent levels of tectonic stress, which could be the risk factor for generating large earthquakes in the future [ 54 56 ]. The area identified as high risk zone in this study is within the zone identified as anomalous seismicity zone in the past work [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The smaller b-value zones (0.48–0.60) are corroborated with higher D 2 (1.5–1.9), implying negative correlation. The areas with low b-value and high D 2 and are expected to accumulate prominent levels of tectonic stress, which could be the risk factor for generating large earthquakes in the future [ 54 56 ]. The area identified as high risk zone in this study is within the zone identified as anomalous seismicity zone in the past work [ 21 ].…”
Section: Discussionmentioning
confidence: 99%